(untitled) (VERITAS LEGIS JOURNAL, 2026)
Ten years have passed since the adoption of the Entrepreneurial Code of the Republic of Kazakhstan (hereinafter referred to as the EC). During this time, it has become the primary legal document regulating the relationship between government bodies and entrepreneurship as an organized social force. Entrepreneurs actively utilize intellectual property rights (hereinafter referred to as IP), enshrined in a variety of sources, including the EC. Moreover, the EC’s intellectual property provisions fall within the "rights relating to unfair competition" group of IP rights, as defined by Article 1 of the WIPO Convention. This group of rights has been very poorly studied in Kazakh and Russian legal literature. The purpose of this article is to examine the specific features of the EC’s IP provisions. To this end, the objectives are to demonstrate the composition and features of the legal norms on IP enshrined in the Entrepreneurship Code, from the perspective of their place in the classification of IP rights under the aforementioned WIPO Convention, their relationship with the classification of IP objects in the Civil Code of the Republic of Kazakhstan, and to characterize the social function these norms perform in achieving fair competition. Results: The Entrepreneurship Code contains norms that expand the range of protected IP objects. It is established that the Entrepreneurship Code filled a regulatory gap in the legislation of the Republic of Kazakhstan, which did not fully cover intellectual property rights related to unfair competition, a gap that arose at the time of the adoption of the Entrepreneurship Code. These norms position the Entrepreneurship Code as a crucial deterrent to unfair competition. It is proposed to supplement Article 961 of the Civil Code of the Republic of Kazakhstan with provisions on unfair competition. Thus, this article contains a number of proposals for improving the norms governing IP and performing functions to limit unfair competition.